2005
DOI: 10.1021/jp046132m
|View full text |Cite
|
Sign up to set email alerts
|

Oxo−Hydroxy Tautomerism of 5-Fluorouracil:  Water-Assisted Proton Transfer

Abstract: Post-Hartree-Fock ab initio quantum chemical calculations were performed for 5-fluorouracil in the gas phase and in a three-water cluster. Full geometry optimizations of the 5-fluorouracil-water complexes were carried out at the MP2/6-31+G(d,p) level of theory. MP4/6-31+G(d,p)//MP2/6-31+G(d,p) and MP4/6-31++G(d,p)//MP2/6-31+G(d,p) single-point calculations were performed to obtain more accurate energies. In water solution, 5-fluorouracil exists mainly in the 2,4-dioxo form (A). We propose that the populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…12,13,24,25 These studies showed that water molecules decrease the activation energies of the proton transfers. 12,13,24,25 These studies showed that water molecules decrease the activation energies of the proton transfers.…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation
“…12,13,24,25 These studies showed that water molecules decrease the activation energies of the proton transfers. 12,13,24,25 These studies showed that water molecules decrease the activation energies of the proton transfers.…”
Section: Tablementioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Furthermore, some studies have been performed on the reactions of uracil and its interaction with other molecules. Many researchers have studied structures of different tautomers of uracil as well as their stability in the gas and solution phases.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the proton transfer A0 ↔ B0 [Scheme (c)] was investigated using ab initio methods. The previous studies on formamide and many other systems indicated that the water molecules around play an important role and assist the proton transfer processes 6, 15, 37–42. Here, the solvent effects on the present A0 ↔ B0 tautomerization processes were considered in two different ways: (a) Interactions with one and two discrete water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In chemical terms 5-fluorouracil is an aromatic compound, whose most stable tautomer in a neutral medium is the diketone form ( Fig. 1) (Marino et al, 1997;Markova et al, 2005Markova et al, , 2010Pavel et al, 2005;Yekeler and Ozbakır, 2001). In water it dissolves better (85.1 mM (Sloan et al, 2005), 96.9 mM (Singh, 2005), 138.2 mM (Szterner, 2008)) than in ethanol (<1 mM, (Kobayashi et al, 1998)).…”
Section: Introductionmentioning
confidence: 99%